PENGEMBANGAN BAHAN AJAR DALAM PEMBELAJARAN TEKS NEGOSIASI BERBASIS DISCOVERY LEARNING PADA SISWA KELAS X MA DARUL ULUM PASINAN BAURENO - Hendrik Furqon; Hanida Ika Pradita (MIDA : Jurnal Pendidikan Dasar Islam, 2023)
Abstract Based on the K13 curriculum, the Indonesian language learning requires a new innovation in terms of the teaching and learning aspects that are used by students. The majority of the 2013 curriculum learning is using my mother's package, which was inaugurated by the government. The Packet book is like the LKS, which makes students bored and lazy to study it. My mother, the package, is still less valid, less effective, and less interesting, so students are less iterative in the material, this is the only thing. Negotiation text learning requires a learning model that can involve students in searching for and investigating themselves in solving problems. The ilearning model is the learning discovery model. The objectives of this research include: (1) to describe the validity and attractiveness of teaching and learning activities, (2) to describe the effectiveness of teaching materials, (3) to describe the attractiveness of students towards teaching learning. This research is a type of R&D development research using the qualitative and quantitative research method as well as the ADDIE development model. The steps in the teaching development process include: (1) product design, (2) product validation test, (3) product revision, and (4) product testing. The subjects of this. research were chosen according to their needs, namely: (1) expert test takers content and design, (2) effectiveness experts, and (3) students. Based on analysis, the results of validity test and expert content test are i83.8% with category very good, the test of effectiveness of teaching-learning item is i86.8% with category very small very good, ari-test is very good The test for the attractiveness of the wide-ranging students got a score of 88.6%, with an very good category. Keywords: development, teaching change, attractiveness, negotiation items, Discovery Learning model Abstrak Berlandaskan kurikulum K13, pembelajaran bahasa Indonesia menuntut adanya sebuah inovasi baru dari segi pembelajaran dan bahan ajar yang digunakan siswa. Pembelajaran kurikulum 2013 adalah menggunakan Lembar Kerja Siswa (LKS) yang diresmikan pemerintah. LKS membuat siswa bosan dan malas untuk mempelajarinya, buku paket tersebut masih kurang valid, kurang efektif, dan kurang menarik sehingga siswa kurang tertarik dengan materi di dalamnya, salah satunya adalah teks negosiasi. Pembelajaran teks negosiasi memerlukan model pembelajaran yang dapat melibatkan siswa untuk mencari dan menyelidiki sendiri dalam menyelesaikan masalah. Model pembelajaran tersebut adalah model discovery learning. Adapun tujuan dalam penelitian ini, meliputi: (1) mendeskripsikan kevalidan bahan ajar, (2) mendeskripsikan keefektifan bahan ajar, (3) mendeskripsikan kemenarikan siswa terhadap bahan ajar. Penelitian ini merupakan jenis penelitian pengembangan R&D dengan menggunakan metode penelitian kualitatif dan kuantitatif serta model pengembangan ADDIE. Langkah-langkah proses pengembangan bahan ajar meliputi: (1) mendesain produk, (2) uji validasi produk, (3) revisi produk, dan (4) uji coba produk. Subjek penelitian ini dipilih sesuai dengan kebutuhan yaitu: (1) validator ahli isi dan desain, (2) ahli keefektifan, dan (3) siswa. Berdasarkan analisis diperoleh hasil uji kevalidan ahli isi dan desain sebanyak 83.8% dengan kategori sangat baik, uji efektifitas bahan ajar teks negosiasi sebanyak 86.8% dengan kategori sangat baik, uji kemenarikan siswa skala kecil sebanyak 88% dengan kategori sangat baik, dan uji kemenarikan siswa skala luas mendapatkan nilai sebanyak 88.6% dengan kategori sangat baik. Kata Kunci: pengembangan, bahan ajar, keefektifan, teks negosiasi, model Discovery Learning